Socio-Economic Status and Structural Constraints of Tharu Women Farmers in Chitwan, Nepal - Raut, Rekha; Shrestha, Mohan Kumar (ILAM इलम, 2026)
This study aims to examine the role that the Tharu women play in the decision-making vegetable economy in the District of Chitwan. The study employed a mixed-method approach where quantitative data were taken from systematically sampled 267 Tharu women farmers. Similarly, qualitative data were taken from the interviews with community leaders. The descriptive statistics and a multilinear regression model were used to analyse quantitative data. The findings have shown that there are a lot of mismatches between the input of women to the workforce and the strength of women in determining the economy. Tharu women undertake the more physically exhausting tasks of weeding (85.4 percent) and harvesting (78.3 percent). However, the share of value that they control is negligeable, with only 11.6 per cent owning the land in which they worked outright, and few of them (15.7 per cent and 22.1 per cent) were engaged in activities of higher value, like marketing, and finance management. The most influential positive factors of income determine by the regression analysis to be the size of the landholding (8=.45) and access to agricultural training (1=.28). In sum, the paper has indicated that even though vegetable farming is an important livelihood system, it does not empower Tharu women because the structural imbalance is very deep rooted. The vegetable economy of Chitwan, where Tharu women form the workforce, supplies most manual labour, including weeding (85.4) and harvesting (78.3) the products, and earn 65 per cent of household income. They are however restricted in a labour only form; a mere 11.6% owning land and less than 10% negotiating in the markets they do not have the structural capacity to dictate on the financial decisions or even the value chain as a whole.